Modeling of outdoor natural ventilation and energy performance for buildings in an industrial park - Yan, Naung Thein (Nanyang Technological University, 2020)
This project consists of a CFD analysis of 10 different models. The models are set of 4 buildings with the constant volume and height. Furthermore, the shapes are arranged in a different way and the ventilation and temperature distribution around the buildings are analyzed. The major difference in the models is that there are 5 designs with a gap of 5 meters and another 5 similar design models with the gap of 30 meters in between each building. The CFD analysis contains the streamlines flow, and temperature contours at different planed and locations. After commenting on the results obtained and analyzing the output it is found that the models with the gap of 30 meters and circular building shape are better for ventilation as well as for maintaining the temperature as low as possible.